Effects of maternal proteic undernutrition on the neurons of the myenteric plexus of the duodenum of rats Efeitos da desnutrição proteica materna sobre os neurônios do plexo mientérico do duodeno de ratos - Maria Raquel Marçal Natali; Marcílio H. Miranda-Neto (Arquivos de Neuro-Psiquiatria)
The purpose of this study was to verify the effects of proteic undernutrition on the neurons of the myenteric plexus from the duodenum of Wistar rats. Twenty-four animals at the age of 60 days were divided in four groups, which were named according to the period their mothers received hypoproteic ration (8%). Some segments of duodenum were subjected to histological treatment and stained with hematoxilin-eosin and some were used for whoie mount preparations stained with Giemsa. We observed small, medium-sized and large neurons grouped in ganglia of various shapes. It was concluded that the maternal proteic undernutrition does not affect the organization of the myenteric plexus and that animals submitted to undernutrition during gestation and lactation, when normally fed, show neurons with strongly basophilic cytoplasm and larger cellular bodies than those from control animals. O propósito deste estudo foi investigar os efeitos da desnutrição proteica sobre os neurônios do plexo mientérico do duodeno de ratos Wistar. Vinte e quatro animais com 60 dias de idade foram divididos em 4 grupos e denominados de acordo com o período em que suas mães receberam ração hipoproteica (8%). Alguns segmentos de duodeno foram submetidos a tratamento histológico e corados com hematoxilina-eosinae alguns foram utilizados na elaboração dos preparados de membrana corados com Giemsa. Observamos neurônios pequenos, médios e grandes formando gânglios de formatos diversos. Concluiu-se que a desnutrição proteica materna não afeta a organização do plexo mientérico e que animais desnutridos na gestação e lactação quando voltam a receber dieta com teor proteico normal apresentam neurônios com citoplasma fortemente basofílico e geralmente maiores que o de animais normo-alimentados.